(untitled) (Research, Society and Development, 2023)
Introduction: The use of psychoactive substances has currently been a social, economic and political problem of great relevance and worldwide scope, involving different layers of society. Objective: to analyze in the current literature the importance of psychosocial support in therapeutic communities, as well as to describe the main psychological actions in these social spaces and identify how the family and society contribute to the work of Therapeutic Communities in relation to chemical dependency. Method: Integrative literature review of articles indexed in the databases of the Coordination for the Improvement of Higher Education Personnel, the Scientifi Electronic Library Online and the National Library of Medicine. Results: the final sample consisted of 12 publications that proved to be efficient in relation to the topics addressed, however there was a limitation regarding the benefits of psychological care for people who live in therapeutic communities. Conclusion: professionals who work in therapeutic communities need to have a more humanized look at inmates and family members as they are products of a society that excludes and marginalizes those who are different, thus in need of attention and care.